Analysis of modified linear congruential generator for the randomness property - Abd Ghani, Aniza; Mohd Zamulud, Balqis (Universiti Putra Malaysia Press, 2024)
Linear Congruential Generators (LCGs) are fundamental tools in the generation of pseudo-random numbers, playing a crucial role in various computational applications. This study delves into the analysis and enhancement of LCG through the modification of utilizing inverse modular multiplication designed to address the limitations. This research paper is done to study the modified LCG by generating the sequence, determine the randomness property of modified LCG by utilizing the NIST Statistical Test Suite and comparing the randomness of the sequence generated by the standard LCG with the modified LCG using the empirical results obtained from the statistical tests. Investigation and analysis of randomness are discussed to show that the modified LCG is a better generator to generate the keystream sequence. Finding shows that the standard LCG sequences failed the randomness test while the modified LCG passed the test. Therefore, it can be concluded that the generated sequence using the modified LCG is more random than sequence generated using the standard LCG.